Validation of particle and heavy ion transport code system (PHITS) in generating dose-voxel kernels for internal dosimetry calculations - Tatu, Shalaine Sana; Kelley, Brian M.; Wong, Yin How; Kasbollah, Azahari; Suppiah, Subapriya; Zhi Xin, Phuna; Kappadath, S. Cheenu; Yeong, Chai Hong (Springer Nature, 2025)
Purpose In voxel-based dosimetry, dose-voxel kernels (DVKs) represent the absorbed dose in a target voxel per decay in a source voxel. In this work, we aimed to validate DVKs generated using Particle and Heavy Ion Transport Code System (PHITS) as a first step in establishing a quantitative SPECT/CT-based dosimetry framework for selective internal radiation therapy (SIRT).